Pre-treatment maximum standardized uptake value predicts outcome after frontline therapy in patients with advanced stage follicular lymphoma - Strati, Paolo (Haematologica, 2020)
The impact of pre-treatment maximum standardized uptake value (SUV(max)) on the outcome of follicular lymphoma (FL) following specific frontline regimens has not been explored. We performed a retrospective analysis of 346 patients with advanced stage follicular lymphoma (FL) without histological evidence of transformation, and analyzed the impact of SUV(max) on outcome after frontline therapy. Fifty-two (15%) patients had a SUV(max) >18, and a large lymph node ≥6 cm was the only factor associating with SUV(max) >18 on multivariate analysis (odds ratio 2.7, 95% confidence interval [CI]: 1.3-5.3, P=0.006). The complete response rate was significantly lower among patients treated with non-anthracycline-based regimens if SUV(max) was >18 (45% vs. 92%, P<0.001), but not among patients treated with R-CHOP (P=1). SUV(max) >18 was associated with significantly shorter progression-free survival among patients treated with non-anthracycline-based regimens (77 months vs. not reached, P=0.02), but not among patients treated with R-CHOP (P=0.73). SUV(max) >18 associated with shorter overall survival (OS) both in patients treated with R-CHOP (8-year OS 70% vs. 90%, P=0.02) and non-anthracycline-based frontline regimens (8-year OS 50% vs. 85%, P=0.001). In conclusion, pre-treatment PET scan has prognostic and predictive value in patients with advanced stage FL receiving frontline treatment.